Optimal Approach for Assessing Evidence of Dementia for Research Studies. (March 2023) - Resnick, Barbara; Boltz, Marie; Galik, Elizabeth; Ellis, Jeanette; Kuzmik, Ashley; Drazich, Brittany
The purpose of this study was to describe a process to determine the presence of dementia and test the psychometric properties of the proposed measurement model for dementia. The model included the AD8, the Functional Activities Questionnaire, the Clinical Dementia Rating Scale, and the Saint Louis University Mental Status Examination. A total of 346 patients consented and 176 of those were determined to be eligible as a result of screening with this measurement model. The mean age of the participants was 80.70 ( SD  = 9.60) and the majority were female (64%), white (66%), not Latinx (99%), and not married (67%). There was evidence of reliability based on the internal consistency of the items on all measures and the limited error associated with each item. There was evidence of construct validity based on model fit. All four measures are recommended as a pragmatic way in which to comprehensively determine evidence of dementia for research studies.